The Influence Stress Work, Behavior Caring Nurses and Work Culture on Service Excellence in Inpatient at Dharmais Cancer Hospital - Santy Baktirany; Muh. Natsir Nugroho; Rian Adi Pamungkas (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
This study aims for test influence work stress, nurses' caring behavior and work culture towards service excellence. This research uses a survey method, namely research that takes samples from a population using a questionnaire as the main data collection tool to study symptoms. or phenomenon Which observed. Study This use design causality based on dimensions time, that is, measurements of the independent and dependent variables are carried out at the same time. The unit of analysis is the individual, and the data analysis method uses correlation and regression. The sample used in this study is study This is nurse in Care Stay Hospital Dharmais Cancer Which amount to 249 respondents. Data research obtained from results filling questionnaire And analyzed with use technique analysis SEM PLS with the help of program Smart PLS. Results this research show that (1) stress Work negative impact and significant towards service excellence, the higher the nurse's work stress, the lower it is excellent service nurses, and vice versa lower stress Work nurse so increasingly supported by service excellence nurse. Stress Work proven is Wrong One factor Which affect service excellence; (2) behavior caring nurse influential positive to service excellence Which means that that The higher the nurse's caring behavior, the higher the service excellence, and vice versa, the lower the caring behavior. Caring nurse so the more low service excellence. Behavior caring nurse proven is wrong one factor which affect service excellence; (3) culture work no influential towards service excellence and it can be concluded that work culture has not been proven to be a factor that influences service excellence.